2010
DOI: 10.1136/ip.2009.024414
|View full text |Cite
|
Sign up to set email alerts
|

Population density and mortality among individuals in motor vehicle crashes

Abstract: The inverse relationship between population density and mortality among individuals in motor vehicle crashes is related to pre-crash factors that influence the type and severity of injuries and not to differences in EMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 33 publications
1
7
0
3
Order By: Relevance
“…In all three of the models presented, the risk of an adverse outcome increased as rurality increased, as seen in previous research (Baker et al, 1987; Brown et al, 2000; Gedeborg et al, 2010; Goldstein et al, 2011; Muelleman et al, 2007). In particular, individuals with severe injuries were more likely to die in rural counties, validating previous studies (Brodsky and Hakkert, 1983; Brown, 1979; Muelleman et al, 2007; Travis et al, 2012).…”
Section: Discussionsupporting
confidence: 82%
“…In all three of the models presented, the risk of an adverse outcome increased as rurality increased, as seen in previous research (Baker et al, 1987; Brown et al, 2000; Gedeborg et al, 2010; Goldstein et al, 2011; Muelleman et al, 2007). In particular, individuals with severe injuries were more likely to die in rural counties, validating previous studies (Brodsky and Hakkert, 1983; Brown, 1979; Muelleman et al, 2007; Travis et al, 2012).…”
Section: Discussionsupporting
confidence: 82%
“…Each SRR is equal to the proportion of patients who survived with a specific ICD-code in a reference population. In studies with large samples, the study sample is often used as the reference population [35], [36]. Smaller studies may use published SRRs from a larger, similar, reference population [37].…”
Section: Methodsmentioning
confidence: 99%
“…Maio, Green, Becker, Burney, and Compton (1992) and Chen, Maio, Green, and Burney (1995) found evidence that the increased rural mortality might be due to older age, more use of alcohol, higher speeds, or other pre-crash factors, but no evidence that the quality of medical care in rural areas is inferior to that in urban areas. Muelleman, Wadman, Tran, Ullrich, and Anderson (2007) found that the rural risk in Nebraska was higher even after controlling for injury severity, but Gedeborg et al(2010) found no increased rural risk in Sweden after controlling for injury severity.…”
Section: Discussionmentioning
confidence: 98%